Peran KKN Dalam Hubungan Pola Asuh Orang Tua dan Anak di Kampung Selaawi Wangunsari Dengan Program Parenting - Nurul Shafa, Nabilah Siti; Saepudin Rahmatullah; Mira Maulidi; Rachel Diandra (PROCEEDINGS UIN SUNAN GUNUNG DJATI BANDUNG, 2023)
The role of parents at home as the first education is very important which has an impact on the formation of the character of each child. However, sometimes parents still make mistakes that make children have negative traits and are feared to have an impact on their environment and life in the future. So special treatment is needed that is deemed appropriate to solve the problems experienced by children. Including the parenting problem that occurred in Kampung Selaawi, a village located in the West Bandung Regency, Sindangkerta District. The method used in this study using a qualitative approach with descriptive methods. The results of this study are that Selaawi Village, Wangunsari Village, West Bandung Regency needs to build and understand children’s characteristics such as building emotions, communicating well, teaching responsibility, supervising and providing understanding for everything that is done but still listening to children’s opinions.